Safety evaluation of the food enzyme phospholipase C from a genetically modified Komagataella phaffii (strain PRF). (26th April 2019) - ,; Silano, Vittorio; Barat Baviera, José Manuel; Bolognesi, Claudia; Brüschweiler, Beat Johannes; Cocconcelli, Pier Sandro; Crebelli, Riccardo; Gott, David Michael; Grob, Konrad; Lampi, Evgenia; Mortensen, Alicja; Rivière, Gilles; et al.
Abstract: The food enzyme phospholipase C (EC 3.1.4.3) is produced with a genetically modified Komagataella phaffii (formerly Pichia pastoris ) (strain PRF) by DSM. The genetic modifications do not give rise to safety concerns. The food enzyme is free from viable cells of the production organism and recombinant DNA. This phospholipase C is intended to be used in fats and oils processing for degumming. The residual amounts of total organic solids (TOS) are removed during refinement steps applied during fats and oils processing. Consequently, no dietary exposure was calculated. Genotoxicity tests did not indicate a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level (NOAEL) of at least 1, 672 mg TOS/kg body weight per day, the highest dose tested. Similarity of the amino acid sequence to those of known allergens was searched and no match was found. The Panel considered that, under the intended conditions of use, the risk of allergic sensitisation and elicitation reactions by dietary exposure cannot be excluded, but the likelihood is considered to be low. Based on the data provided and the removal of TOS during the fats and oils processing for degumming, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.